Application of Magnetic Nano-Immobilized Enzyme in Soybean Oil Degumming: Numerical Simulation in a Liquid-Solid MFB - Kuiren Chen; Tong Wang; Hong Wang; Haoyuan Geng; Jing Du; Dianyu Yu; Walid Elfalleh; Zouhaier Mehrez; Liqi Wang (Journal of Food Quality)
Using crude soybean oil (CSO) as fluid and nanomagnetic immobilized phospholipase C (PLC) as fluidizing particles, the Eulerian–Lagrangian fluid-particle two-phase flow model was used to numerically simulate the law of motion of fluidizing particles in the magnetic fluidized bed (MFB). The main parameters were obtained by numerical simulation based on the discrete element method (DEM). The nanomagnetic PLC in the MFB was optimal to the enzymatic reaction by limiting the iteration step size to 3 × 10−5, the boundary condition to 20 × 300 mm, the opening rate to 37.5%, the condition of CSO flow rate to 0.01 m/s, and the magnetic field strength to 0.02T. After 2.0 h of reaction, the amount of residual phosphorus in the oil was 55.73 mg/kg, the content of 1, 2-DAG was 1.42%, and the nanomagnetic enzyme still had 97% relative activity. Hence, these optimal conditions can improve the efficiency and the stability of the nanomagnetic enzymatic reaction.